STUDI PENGELOLAAN AIR BERSIH DAN SANITASI DI WILAYAH PESISIR KECAMATAN BONTOA, KABUPATEN MAROS - Akrim, Djusdil; Yusuf, Rumpang; Latif, Rudi; Yuniarto, Eko (Program Studi Teknik Lingkungan Universitas Bosowa, 2025)
The purpose of this study was to determine the existing condition of Clean Water infrastructure facilities in the Coastal Area of Tupabbiring and Bontobahri, Bontoa District, Maros Regency. The research method used is Problem Identification and Potential Analysis (IMAP). The findings in the form of clean water facilities and infrastructure in Tupabbiring and Bontobahari Village are classified as less than good because there is no PDAM water source, so that almost all people collect rainwater and use the water for bathing, washing and even drinking water sources. This can pose a serious health risk because bacterial contamination from rainwater and rusty roofs can cause various diseases. This condition shows the need to increase awareness of good health and sanitation. As well as the urgency of providing safe and sustainable access to clean water for the people of Tupabbiring and Bontobahari village